2018
DOI: 10.1002/ppul.24039
|View full text |Cite
|
Sign up to set email alerts
|

Ribcage deformity and the altered breathing pattern in children with osteogenesis imperfecta

Abstract: An altered breathing pattern in severe OI is present since childhood and it worsens with age. This is caused by the combination of pectus carinatum, brittle ribs and spinal deformity that put the ribcage muscles in mechanical disadvantage. These results suggest that in severe OI the assessment of the respiratory function should start in early childhood in order to try to reduce the incidence of premature death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…We believe that this interaction is mediated more by the combination of spinal and ribcage deformities rather than by the single one. Indeed, we have previously shown that the altered breathing pattern in severe OI worsens with age as a consequence of the combination between the congenital pectus carinatum and spinal deformity that starts in later childhood to develop thereafter [10]. The results of the present study seem to go towards this direction, with the combining index of deformity signi cantly being higher in OSA group.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We believe that this interaction is mediated more by the combination of spinal and ribcage deformities rather than by the single one. Indeed, we have previously shown that the altered breathing pattern in severe OI worsens with age as a consequence of the combination between the congenital pectus carinatum and spinal deformity that starts in later childhood to develop thereafter [10]. The results of the present study seem to go towards this direction, with the combining index of deformity signi cantly being higher in OSA group.…”
Section: Discussionsupporting
confidence: 73%
“…For a respiratory point of view, OI is classi ed as a restrictive disease [6][7][8][9]. The two main factors predisposing to restricted respiratory problems in severe OI are severe kyphoscoliosis and structural modi cations of the ribcage, with the most important effect being thoraco-abdominal asynchrony with thoracic paradoxical inward movement [8,10,11]. Because in the most severe OI form these alterations systematically occur at rest in supine position, we wonder if they may negatively affect sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Tidal breathing analysis is a noninvasive method to assess respiratory function that does not require sedation . LoMauro et al evaluated the chest geometry and breathing pattern in children with severe and mild osteogenesis imperfecta (OI) using opto‐electronic plethysmography (OEP). They demonstrated that the abdominal muscle contribution to tidal volume was increased, the pulmonary rib cage contribution to tidal volume was decreased and the sternal angle was lower in OI children, indicating a mechanical disadvantage for respiratory function.…”
Section: Introductionmentioning
confidence: 99%
“…The association of OI and chest wall deformities has been reported but is infrequent. 5 6 7 LoMauro et al evaluated pulmonary function in 22 patients with OI and found 7 cases of PC; all had Type III OI. 6…”
Section: Introductionmentioning
confidence: 99%